Technical and economic evaluation of renewable energy production in the Italian agricultural firm: financing a biogas plant investment. (20th September 2019) - Raucci, Domenico; Agostinone, Stefano; Carnevale, Martina
This paper provides a technical and economic evaluation for financing a biogas plant investment for energy production. Using a case study, the analysis is focused on a diversification strategy of an Italian agricultural firm that, moving from its 'traditional' business, exploits the potentials offered by the integrations with renewable energy production. The building of a biogas plant represents, for a farm, an opportunity to plan a fruitful sustainable development by searching an effective and efficient balance between the financing sources and the regulatory incentives. The economic-financial results show that the renewable energy investment, especially in the biogas production, integrates effectively the current activities of the farm investigated without changing the 'core' business efficiency. Furthermore, it supports its growth strategies with suitable levels of the profitability and greater attention of environmental impacts.